2013
DOI: 10.1007/s00355-013-0727-1
|View full text |Cite
|
Sign up to set email alerts
|

Equity and effectiveness of optimal taxation in contests under an all-pay auction

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The first one combines the optimal multiplicative bias with the optimal level of noise: either r = 2 or r = ∞ Nitzan, 2011, 2013). The second one combines the optimal modification of valuations through an additive tax and the optimal level of noise: either r = 2 or r = ∞ (Mealem and Nitzan, 2014). conclude that total effort could reach v 1 by combining the optimal level of noise r = ∞ and an optimal combination of multiplicative and additive bias.…”
Section: Comparison and Combination Of Multiple Mechanismsmentioning
confidence: 99%
“…The first one combines the optimal multiplicative bias with the optimal level of noise: either r = 2 or r = ∞ Nitzan, 2011, 2013). The second one combines the optimal modification of valuations through an additive tax and the optimal level of noise: either r = 2 or r = ∞ (Mealem and Nitzan, 2014). conclude that total effort could reach v 1 by combining the optimal level of noise r = ∞ and an optimal combination of multiplicative and additive bias.…”
Section: Comparison and Combination Of Multiple Mechanismsmentioning
confidence: 99%
“…Such a policy is usually based on a "give and take" mechanism in case of winning, which is henceforth referred to as direct discrimination. This form of discrimination has been recently introduced in Mealem and Nitzan (2013) and extensively discussed, focusing on its comparative application in an all-pay-auction relative to a logit CSF.…”
Section: Introductionmentioning
confidence: 99%
“…Such interest groups are typically represented by lobbyists who are the actual contestants. Mealem and Nitzan (2013) have shown that discrimination implemented by taxing and subsidizing the prize subject to a balanced budget constraint is also effective when applied independently.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations